Zebrafish (Danio rerio) as an ecotoxicological model for Nanomaterial induced toxicity profiling - Suresh K Verma; Aditya Nandi; Adrija Sinha; Paritosh Patel; Ealisha Jha; Swabhiman Mohanty; Pritam Kumar Panda; Rajeev Ahuja; Yogendra Kumar Mishra; Mrutyunjay Suar (Precision Nanomedicine, 2021)